STRATEGI PENGEMBANGAN USAHA JASA BOGA DI KECAMATAN TEMBALANG KOTA SEMARANG DENGAN METODE SWOT DAN QSP - Lulu Ikbar Yorinda; Siti Arbainah; Ardian Widiarto (Politeknik Negeri Semarang, 2023)
The catering service businesses in Tembalang District, Semarang City have experienced a decline in sales due to Covid-19 and has a fairly tight level of competition so that the catering businesses requires a business development strategy in order to survive and be superior to competitors. This research is a qualitative descriptive study with data collection through interviews, questionnaires, and observations. Data analysis used IFE matrix, EFE matrix, CPM, IE, SWOT, and QSPM. The total weighted score of the IFE matrix is 2.875 and the EFE matrix is 2.978. Based on CPM, the most superior catering service business is the Artanti Snack and Catering with a total weighted score of 2.960. The results of the IE matrix analysis shows that the position of the catering businesses is in quadrant V (hold and maintain) with the resulting strategy, namely market penetration and product development which is then processed with the SWOT matrix and produces eight (8) alternative strategies. The most suitable strategy based on QSPM is to maintain product quality with a TAS value of 6.504